2003
DOI: 10.1074/jbc.m301359200
|View full text |Cite
|
Sign up to set email alerts
|

2-Arachidonoylglycerol Induces the Migration of HL-60 Cells Differentiated into Macrophage-like Cells and Human Peripheral Blood Monocytes through the Cannabinoid CB2 Receptor-dependent Mechanism

Abstract: 2-Arachidonoylglycerol is an endogenous ligand for the cannabinoid receptors (CB1 and CB2) and has beenshown to exhibit a variety of cannabimimetic activities in vitro and in vivo. Recently, we proposed that 2-arachidonoylglycerol is the true endogenous ligand for the cannabinoid receptors, and both receptors (CB1 and CB2) are primarily 2-arachidonoylglycerol receptors. The CB1 receptor is assumed to be involved in the attenuation of neurotransmission. On the other hand, the physiological roles of the CB2 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
104
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 44 publications
8
104
1
Order By: Relevance
“…Consistent with their anti-inflammatory role observed in CB 2 receptor-deficient mice, endocannabinoids can inhibit chemotaxis and the production of cytokines ex vivo (15)(16)(17)(18)(19)(20). However, an increasing body of evidence also demonstrates that like eicosanoids, endocannabinoids can stimulate proinflammatory functions of myeloid cells, such as cell adhesion, chemotaxis, phagocytosis, and the release of cytokines (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 86%
“…Consistent with their anti-inflammatory role observed in CB 2 receptor-deficient mice, endocannabinoids can inhibit chemotaxis and the production of cytokines ex vivo (15)(16)(17)(18)(19)(20). However, an increasing body of evidence also demonstrates that like eicosanoids, endocannabinoids can stimulate proinflammatory functions of myeloid cells, such as cell adhesion, chemotaxis, phagocytosis, and the release of cytokines (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 86%
“…Conversely, two groups have shown recently that CB 2 activation also promotes microglial migration and proliferation (Walter et al, 2003;Carrier et al, 2004). Furthermore, CB 2 activation enhances human macrophage-like and peripheral blood monocyte migration after CB 2 activation (Derocq et al, 2000;Kishimoto et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We found that 2-AG induces the following: 1) a Ca 2ϩ transient in HL-60 cells (21); 2) the activation of p42/44 MAPK (22); 3) augmented production of chemokines such as IL-8 in HL-60 cells (23); and 4) migration of HL-60 cells that had differentiated into macrophage-like cells (24), human NK cells (25), and eosinophils (26), through CB2 receptorand Gi/o-dependent mechanisms. Several investigators also demonstrated that 2-AG induced the migration of mouse splenocytes (27), microglia cells (28), and dendritic cells (29).…”
Section: Involvement Of the Cannabinoid Cb2 Receptor And Its Endogenomentioning
confidence: 99%